Power module frame material, power module and method of manufacturing power module
Patent Information
- Application Number
- JP2023139258
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-03-13
AI Technical Summary
【0008】 本発明によれば、パワーモジュールを製造する際や使用時において、反りの発生が抑制されたパワーモジュール用枠材、当該枠材を備えるパワーモジュールおよびパワーモジュールの製造方法を提供することができる。
Smart Images

Figure 2025033502000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a frame material for a power module, a power module including the frame material, and a method for manufacturing the power module. [Background technology]
[0002] High-power density power modules that are used in electric vehicles, trains, and aircraft have a case-type structure. Case-type power modules are constructed in such a way that semiconductor devices, including power semiconductor elements such as IGBTs, power MOSFETs, and diodes, are sealed inside a resin case (frame material).
[0003] Patent Document 1 discloses a power module having a resin case made of a thermally conductive resin composition containing a predetermined thermoplastic resin, a thermally conductive filler, and a reinforcing material which is a fibrous filler or a needle-like filler. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-116421 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the power module having the resin case described in Patent Document 1, warping occurs in the insulating case during the manufacture and use of the power module, leaving room for improvement in product reliability. [Means for solving the problem]
[0006] The present inventors have found that warping of a resin case is suppressed when the flexural modulus at 150° C. of the resin case (frame material) is within a predetermined range, and have completed the present invention. That is, the present invention can be shown as follows.
[0007] [1] (A) a base substrate having electronic components on one surface; (B) a frame material provided on the surface of the base substrate (A) on which the electronic components are provided so as to surround the electronic components; (C) a sealant that seals the electronic component in an area surrounded by the frame material (B); A frame material (B) in a power module comprising: A frame material for a power module, the frame material (B) having a flexural modulus (150°C) of 6 GPa or more and 30 GPa or less. [2] The frame material for a power module according to [1], wherein the bending strength (150°C) of the frame material is 50 MPa or more and 200 MPa or less. [3] The frame material for a power module according to [1] or [2], wherein the frame material has a glass transition point of 120°C or higher. [4] The frame material for a power module according to any one of [1] to [3], wherein the frame material (B) contains a phenolic resin. [5] (A) a base substrate having electronic components on one surface; (B) a frame material provided on the surface of the base substrate (A) on which the electronic components are provided so as to surround the electronic components; (C) a sealant that seals the electronic component in an area surrounded by the frame material (B); A power module comprising: A power module, wherein the flexural modulus (150°C) of the frame material (B) is 6 GPa or more and 30 GPa or less. [6] The power module according to [5], wherein a value S1 calculated by the following formula is 0.3 or more and 10 or less. Formula: S1 = flexural modulus of frame material (B) (GPa, 150°C) / |(α1-α2)| α1: Linear expansion coefficient of the encapsulant (C) in the vertical direction (ppm / ℃) α2: Linear expansion coefficient of the frame material (B) in the vertical direction (ppm / ℃ [7] The power module according to [5] or [6], wherein the value S2 calculated by the following formula is 0.4 or more and 10 or less. Formula: S2 = flexural modulus of frame material (B) (GPa, 150°C) / |(α2-α3)| α2: Coefficient of linear expansion of the frame material (B) in the vertical direction (ppm / ℃) α3: Linear expansion coefficient of the base substrate (A) in the vertical direction (ppm / ℃) [8] The power module according to any one of [5] to [7], wherein the frame material (B) contains a phenol resin and the sealing material (C) contains an epoxy resin. [9] preparing a frame material (B); A step of fixing a frame material (B) to an upper surface of a base substrate (A) having electronic components thereon so as to surround the electronic components; and filling a space surrounded by the upper surface of the base substrate (A) and the frame material (B) with a sealant to seal the electronic component. A method for manufacturing a power module, wherein the frame material (B) is made of a phenolic resin composition. Effect of the Invention
[0008] According to the present invention, it is possible to provide a frame material for a power module in which the occurrence of warping during the manufacture and use of the power module is suppressed, a power module including the frame material, and a method for manufacturing the power module. [Brief description of the drawings]
[0009] [Figure 1] 1 is a schematic cross-sectional view of a power module including a frame material of the present embodiment. [Diagram 2] Photographs showing the procedure of an experiment for measuring warpage of a frame material in an embodiment. [Diagram 3] 1 is an image showing the measurement results of warpage in Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the embodiments of the present invention will be described with reference to the drawings. In all drawings, the same components are denoted by the same reference numerals, and the description will be omitted as appropriate. For example, "1 to 10" means "1 or more" to "10 or less" unless otherwise specified.
[0011] <Power Module 10> A power module 10 according to this embodiment will be described. 1 is a schematic cross-sectional view showing a power module 10 according to an embodiment of the present invention. In the following, for ease of explanation, the positional relationship (upper / lower relationship, etc.) of each component of the power module 10 may be described as being as shown in each drawing. However, the positional relationship in this explanation is unrelated to the positional relationship during use or manufacture of the power module 10.
[0012] As shown in FIG. 1 , the power module 10 of this embodiment basically comprises a base substrate 14 having electronic components 12 on one surface thereof, a frame material 16 provided on the surface of the base substrate 14 having the electronic components 12 so as to surround the electronic components 12, and a sealing material 18 that seals the electronic components 12 in the area surrounded by the frame material 16.
[0013] An insulating substrate 24 having thin metal films 26 on both sides is mounted on the upper surface of the base substrate 14 via a bonding layer 22 made of sintering paste. The thin metal film 26 is a metal circuit made of copper or aluminum. An electronic component 12 is bonded to the surface of the thin metal film 26 on the upper surface of the insulating substrate 24 via the bonding layer 22. The electronic component 12 is electrically connected via a wire 28 to the thin metal film 26 on which the electronic component 12 is not mounted. A plurality of terminals 30 are provided upright on the thin metal film 26, and are capable of transmitting signals from the electronic component 12 to the outside.
[0014] Frame material 16 has a box shape that is open at the top and bottom, and is provided on base substrate 14 so as to surround electronic component 12 and insulating substrate 24 having metal thin films 26 on both sides. In the area surrounded by frame material 16, electronic component 12, insulating substrate 24, metal thin film 26, and lower portions of terminals 30 are sealed with sealing material 18. Upper portions of terminals 30 are not sealed, and are electrically connected to an external device.
[0015] The base substrate 14 is connected to an external cooling structure 20, such as a heat sink having structures such as heat dissipation fins, to dissipate heat from the electronic component 12.
[0016] [Electronic Components 12] An example of the electronic component 12 is a power semiconductor chip. Examples of the power semiconductor chip include an insulated gate bipolar transistor (IGBT) and a diode. An electrode pattern (not shown) is formed on the upper surface of the power semiconductor chip, and a conductive pattern (not shown) is formed on the lower surface of the power semiconductor chip.
[0017] The lower surface of the power semiconductor chip is bonded to the upper surface of the metal thin film 26 via a bonding layer 22, which is a sintering layer. The electrode pattern on the upper surface of the power semiconductor chip is electrically connected to the metal thin film 26 via a wire 28.
[0018] Power semiconductor chips are, for example, SiC, GaN, Ga 2 O 3 Alternatively, the power semiconductor chip may be a semiconductor made of diamond. The power consumption of the power semiconductor chip is, for example, 2.0 W or more, preferably 3.0 W or more, and may be, for example, 4.0 W or less.
[0019] The voltage of the power semiconductor chip is, for example, 1.0 V or more, preferably 3.0 V or more, and may be, for example, 5.0 V or more. The voltage of the power semiconductor chip 1 may be, for example, 100 V or less.
[0020] The power density of the power semiconductor chip 1 is, for example, 10 W / cm 3 More than 20 W / cm 3 or more, for example, 30 W / cm 3 The power density of the power semiconductor chip 1 may be, for example, 200 W / cm 3The power semiconductor chip 1 can also operate in a high temperature environment at a temperature higher than that of a conventional semiconductor made of Si, for example, at 200° C. or higher.
[0021] [Base board 14] The base substrate 14 is a heat dissipation member, and can be connected to an external cooling structure 20, such as a heat sink, that has a structure such as a heat dissipation fin to dissipate heat from the electronic component 12. The base substrate 14 can be made of a metal such as copper or aluminum.
[0022] [Frame material 16] The frame material 16 is made of resin, and the flexural modulus (150° C.) can be set to 6 GPa or more and 30 GPa or less, preferably 7 GPa or more and 25 GPa or less, and more preferably 8 GPa or more and 20 GPa or less.
[0023] A power module having such a frame material 16 for a power module having excellent mechanical strength when heated suppresses warping of the frame material during manufacture and use of the power module, resulting in excellent product reliability of the power module.
[0024] The bending strength (150° C.) of the frame material 16 can be set to preferably 50 MPa or more and 200 MPa or less, more preferably 60 MPa or more and 190 MPa or less, and further preferably 70 MPa or more and 180 MPa or less. Such a frame material 16 has superior mechanical strength when heated, and therefore the power module 10 including the frame material 16 has superior product reliability.
[0025] The glass transition point of the frame material 16 can be preferably 120° C. or higher, more preferably 150° C. or higher, and even more preferably 180° C. or higher. Since such a frame material 16 has excellent heat resistance, deformation of the frame material 16 due to heat generated when the power module 10 is in use is suppressed.
[0026] In this embodiment, the physical properties of the frame material 16 can be controlled by appropriately selecting the type and amount of each component contained in the frame material 16, the manufacturing method of the frame material 16, and the like. A frame material 16 having such properties can be obtained from a thermosetting resin composition.
[0027] As the thermosetting resin composition, a known thermosetting resin composition can be used as long as the effects of the present invention are achieved. For example, a thermosetting resin composition containing a thermosetting resin (a), calcium hydroxide (b), and calcium carbonate (c) can be mentioned.
[0028] (Thermosetting resin (a)) In this embodiment, the thermosetting resin composition contains a thermosetting resin (a). Examples of the thermosetting resin (a) include phenolic resin, furan resin, epoxy resin, polyacrylonitrile, etc., and one or more of them may be used in combination. In this embodiment, from the viewpoint of the effects of the present invention, it is more preferable to use a phenolic resin, and more preferable to use a resol-type phenolic resin.
[0029] The resol type phenolic resin is a resin obtained by reacting a phenol with an aldehyde in a reaction solvent in the presence of a basic catalyst under the specified conditions described below.
[0030] Phenols used for the synthesis of the resol-type phenolic resin used in this embodiment include phenol; dihydroxybenzenes such as o-dihydroxybenzene (i.e., catechol), m-dihydroxybenzene (i.e., resorcinol, i.e., resorcin), and p-dihydroxybenzene (i.e., hydroquinone); trihydroxybenzenes such as 1,2,3-trihydroxybenzene (i.e., pyrogallol); cresols such as o-cresol, m-cresol, p-cresol, and oxocresol; alkylphenols such as ethylphenol, butylphenol, octylphenol, and nonylphenol; xylenol; 3-pentadecylphenol, 3-pentadecylphenol monoene, 3-pentadecylphenol diene, and 3-pentadecylphenol triene. These include components of cashew oil such as 1,3-dihydroxy-5-pentadecylbenzene, 1,3-dihydroxy-5-pentadecylbenzenemonoene, 1,3-dihydroxy-5-pentadecylbenzenediene, and 1,3-dihydroxy-5-pentadecylbenzenetriene, which are cardol-containing components, 2-methyl-1,3-dihydroxy-5-pentadecylbenzene, 2-methyl-1,3-dihydroxy-5-pentadecylbenzenemonoene, 2-methyl-1,3-dihydroxy-5-pentadecylbenzenediene, and 2-methyl-1,3-dihydroxy-5-pentadecylbenzenetriene, which are methyl cardol-containing components, urushiol, bisphenols such as bisphenol A, bisphenol F, and bisphenol S, p-phenylphenol, and styrenated phenol. These may be used alone or in combination of two or more.
[0031] Examples of aldehydes used for synthesizing the resol-type phenolic resin used in this embodiment include formaldehyde, paraformaldehyde, trioxane, acetaldehyde, propionaldehyde, polyoxymethylene, chloral, hexamethylenetetramine, furfural, glyoxal, n-butylaldehyde, caproaldehyde, allylaldehyde, benzaldehyde, crotonaldehyde, acrolein, tetraoxymethylene, phenylacetaldehyde, o-tolualdehyde, and salicylaldehyde. These may be used alone or in combination of two or more. It is also possible to use precursors of these aldehydes or solutions of these aldehydes. Among these, it is preferable to use an aqueous formaldehyde solution from the viewpoint of production costs.
[0032] Examples of basic catalysts used for synthesizing the resol-type phenolic resin used in this embodiment include hydroxides of alkali metals or alkaline earth metals such as sodium hydroxide, potassium hydroxide, calcium hydroxide, etc.; carbonates such as sodium carbonate, calcium carbonate, etc.; oxides such as lime; sulfites such as sodium sulfite; phosphates such as sodium phosphate; amines such as ammonia, trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, hexamethylenetetramine, pyridine, etc.
[0033] The reaction solvent used for synthesizing the resol-type phenolic resin used in this embodiment is generally water, but an organic solvent may also be used. Specific examples of such organic solvents include alcohols, ketones, aromatics, etc. Specific examples of alcohols include methanol, ethanol, propyl alcohol, ethylene glycol, diethylene glycol, triethylene glycol, glycerin, etc. Specific examples of ketones include acetone and methyl ethyl ketone. Specific examples of aromatics include toluene and xylene.
[0034] The resol type phenolic resin may be in the form of a solid, an aqueous solution, a solvent solution, or an aqueous dispersion. Among these, a solvent solution of methanol, ethanol, methyl ethyl ketone, or acetone is preferred from the viewpoint of good workability.
[0035] The resol type phenolic resin used in this embodiment is obtained by mixing phenols (P) and aldehydes (F) in a molar ratio (F / P) of 1.5 or more, preferably 1.5 to 2.0, more preferably 1.6 to 1.9, and further adding the above-mentioned basic catalyst as a polymerization catalyst, and refluxing for an appropriate time (e.g., 3 to 6 hours). The reaction temperature is, for example, 40°C to 120°C, preferably 60°C to 100°C. This makes it possible to suppress gelation and obtain a resol type phenolic resin with a target molecular weight.
[0036] From the viewpoint of the effects of the present invention, the thermosetting resin composition (100 mass%) of the present embodiment can contain the thermosetting resin (a) in an amount of 5 mass% or more and 60 mass% or less, preferably 10 mass% or more and 50 mass% or less, and more preferably 20 mass% or more and 40 mass% or less.
[0037] (Calcium hydroxide (b)) The thermosetting resin composition of the present embodiment contains 4.3 parts by mass or more and 7.0 parts by mass or less, and preferably 4.8 parts by mass or more and 7.0 parts by mass or less, of calcium hydroxide (b) per 100 parts by mass of the thermosetting resin (a).
[0038] When the amount of calcium hydroxide (b) is within the above range, the cured product obtained from the thermosetting resin composition is suppressed in warping, and a molded product with small anisotropy and suppressed peeling can be obtained. Calcium hydroxide (b) can be used as a hardening aid, and other hardening aids such as magnesium oxide can be included.
[0039] (Calcium carbonate (c)) The thermosetting resin composition of this embodiment may contain calcium carbonate (c) in an amount of 20% by mass or more and 60% by mass or less, preferably 30% by mass or more and 60% by mass or less, and more preferably 40% by mass or more and 60% by mass or less, based on 100% by mass of the thermosetting resin composition.
[0040] When the amount of calcium carbonate (c) is within the above range, a cured product obtained from the thermosetting resin composition can be obtained that is suppressed in warping, has small anisotropy, and is suppressed in peeling. From the viewpoint of the effects of the present invention, it is preferable to combine calcium hydroxide (b) and calcium carbonate (c) within the above-mentioned ranges of addition amounts.
[0041] (Fiber filler (d)) The thermosetting resin composition of the present embodiment may further contain a fibrous filler (d). As the fibrous filler (d), for example, glass fiber, wollastonite fiber, carbon fiber, plastic fiber, etc. can be used. As the plastic fiber, for example, aramid fiber (aromatic polyamide) can be used. In addition, as the fibrous filler, inorganic fiber such as basalt fiber and metal fiber such as stainless steel fiber can also be used.
[0042] Among these, it is preferable to select from the group consisting of glass fiber, wollastonite fiber, and carbon fiber, since this can increase the mechanical strength of the molded article and also contributes to reducing the weight of the molded article, and glass fiber is more preferable.
[0043] When glass fiber is used as the fiber filler (d), specific examples of the glass constituting the glass fiber include E glass, C glass, A glass, S glass, D glass, NE glass, T glass, and H glass. Among these, E glass, A glass, T glass, or S glass is preferable. By using such glass, high elasticity can be achieved and the thermal expansion coefficient can be reduced.
[0044] The number average fiber diameter of the fibrous filler (d) can be appropriately set depending on the application of the molded article, but is preferably 3 μm to 50 μm, more preferably 5 μm to 30 μm, and even more preferably 8 μm to 20 μm. By using a fibrous filler (d) having such a number average fiber diameter, the mechanical strength of the molded article can be improved.
[0045] The number average fiber diameter can be determined by observing and measuring the fibers appearing in the cross section of a molded article using a scanning electron microscope, a transmission electron microscope, an atomic force microscope or the like. For example, when measuring with a scanning electron microscope, an arbitrary number of the fiber fillers (d) can be measured in the cross section of the molded article, and an average value can be calculated. More specifically, after measuring 100 pieces of fiber filler (d) whose cross sections can be confirmed, the average of the smallest diameters of each fiber cross section can be calculated as the number average fiber diameter.
[0046] The thermosetting resin composition (phenolic resin composition) of the present embodiment may contain a fiber filler (d) in an amount of preferably 5% by mass to 40% by mass, more preferably 6% by mass to 30% by mass, based on 100% by mass of the composition. By containing the fiber filler in the above range, the strength of the molded product can be improved, product reliability can be improved, and flowability and filling property can be more effectively improved.
[0047] (Spherical filler (e)) The thermosetting resin composition of the present embodiment may further contain a spherical filler (e). In this embodiment, the spherical filler (e) does not include spherical fillers made of calcium carbonate.
[0048] The thermosetting resin composition of the present embodiment may use, for example, a spherical inorganic filler, such as glass spherical filler (glass beads), glass powder, silica, aluminum hydroxide, clay, etc. Among these, it is preferable to use glass spherical filler because of its high heat resistance and high availability.
[0049] The average particle size of the spherical filler (e) can be appropriately set depending on the application of the molded product, but is preferably 12 μm or more and 100 μm or less, more preferably 15 μm or more and 90 μm or less, and even more preferably 20 μm or more and 80 μm or less. By using the spherical filler (e) having such an average particle size, it is possible to suppress the occurrence of anisotropy in the obtained molded product while ensuring the flowability of the molding material.
[0050] The average particle size of the spherical filler (e), like that of the fibrous filler (d), can be determined by measurement through observation with a scanning electron microscope, a transmission electron microscope, an atomic force microscope or the like.
[0051] In addition, when measuring with a scanning electron microscope, the molded product is fired in an inert atmosphere to remove the organic components, and any number of spherical fillers (e) can be counted from the residue, and an average value can be calculated. More specifically, the average particle size can be determined by measuring 50 points on a sample of the spherical filler (e).
[0052] The thermosetting resin composition of the present embodiment may contain spherical filler (e) in an amount of preferably 3% by mass or more and 30% by mass or less, more preferably 5% by mass or more and 20% by mass or less, based on 100% by mass of the composition. The orientation of the fibrous filler (D) during molding can be made random while ensuring the fluidity of the thermosetting resin composition, and the occurrence of anisotropy in the resulting molded product can be further suppressed. The orientation of the fibrous filler (B1) during molding can be made random while ensuring the fluidity of the molding material, and the occurrence of anisotropy in the resulting molded product can be suppressed.
[0053] (Other Ingredients) The thermosetting resin composition of the present embodiment may contain various additives, for example, release agents such as stearic acid, calcium stearate, and polyethylene, curing assistants such as magnesium oxide, calcium hydroxide, and triphenylphosphine, colorants such as carbon black, adhesion improvers, coupling agents, and solvents, as necessary.
[0054] The thermosetting resin composition of the present embodiment can be produced, for example, by blending and uniformly mixing the above-mentioned components, and then heating and melting and kneading the mixture using a kneading device such as a roll, a co-kneader, or a twin-screw extruder alone or in combination with a roll and another mixing device, followed by granulation or pulverization.
[0055] The frame material 16 can be produced by subjecting the thermosetting resin composition (phenolic resin composition) of this embodiment to a known molding method such as compression molding or transfer molding.
[0056] [Sealing material 18] The sealing material 18 is, for example, a molding resin, and seals the electronic components 12, the insulating substrate 24, the metal thin film 26, the lower portions of the terminals 30, etc., integrally inside.
[0057] The encapsulant 6 is composed of a cured product of an encapsulant resin composition. As the encapsulant resin composition, a known encapsulant resin composition can be used within the scope of the effects of the present invention, and examples of the encapsulant resin composition include a encapsulant resin composition containing a thermosetting resin, a curing agent, an inorganic filler, and a curing accelerator.
[0058] The thermosetting resin may be an epoxy resin. The epoxy resin may be an alicyclic epoxy resin, a bisphenol A type epoxy resin, or a bisphenol F type epoxy resin, and may be used alone or in combination of two or more. The thermosetting resin may be contained in an amount of, for example, 2% by mass to 30% by mass based on the entire resin composition. Examples of the hardener include phenol resins and acid anhydrides.
[0059] Examples of the phenol resin include phenol novolac resin, cresol novolac resin, phenol aralkyl resin having a biphenylene skeleton, phenol aralkyl resin having a phenylene skeleton, and phenol resin having a trisphenylmethane skeleton.
[0060] Examples of the acid anhydride include methylhexahydrophthalic anhydride, methyl-5-norbornene-2,3-dicarboxylic anhydride, and methylcyclohexane-1,2-dicarboxylic anhydride. The curing agent can be contained in an amount of 10% by mass to 60% by mass based on the entire resin composition.
[0061] As the inorganic filler, it is preferable to use a silica filler. The silica filler refers to a silica-based filler such as quartz, fumed silica, precipitated silica, silicic anhydride, fused silica, crystalline silica, and ultrafine amorphous silica. The inorganic filler can be contained in an amount of 65% by mass to 85% by mass based on the entire resin composition.
[0062] Examples of the curing accelerator include tertiary amines, quaternary ammonium salts, imidazoles, organic phosphines, Lewis acid catalysts, etc. The curing accelerator may be contained in an amount of 0.03% by mass to 1% by mass based on the entire resin composition. The resin composition for sealing material may contain, as necessary, an anti-settling agent, a coupling agent, a colorant such as carbon black, an anti-foaming agent such as a silicone anti-foaming agent, and the like.
[0063] The above-mentioned resin composition can be poured into the area surrounded by the frame material 16 so as to cover the electronic component 12, the insulating substrate 24, the thin metal film 26 and the lower part of the terminals 30, and then cured to form the sealing material 18.
[0064] In the power module 10 of this embodiment, a numerical value S1 calculated by the following formula can be set to preferably 0.3 or more and 10 or less, more preferably 0.5 or more and 7 or less, and further preferably 0.7 or more and 5 or less. Formula: S1 = flexural modulus of frame material 16 (GPa, 150°C) / |(α1-α2)| α1: Linear expansion coefficient of the sealing material 18 in the vertical direction (ppm / °C) α2: Linear expansion coefficient of the frame material 16 in the vertical direction (ppm / ℃)
[0065] By having the ratio S1 of the bending elastic modulus of the frame material 16 to the difference in the linear expansion coefficients of the sealing material 18 and the frame material 16 within the above range, warping of the frame material 18 is further suppressed and the adhesion between the sealing material 18 and the frame material 16 is excellent.
[0066] In the power module 10 of this embodiment, a numerical value S2 calculated by the following formula can be set to preferably 0.4 or more and 10 or less, more preferably 0.6 or more and 8 or less, and further preferably 0.8 or more and 7 or less. Formula: S2 = flexural modulus of the frame material 16 (GPa, 150°C) / |(α2-α3)| α2: Linear expansion coefficient of the frame material 16 in the vertical direction (ppm / ℃) α3: Linear expansion coefficient of the base substrate 14 in the vertical direction (ppm / °C)
[0067] When the ratio S1 of the flexural modulus of the frame material 16 to the difference in the linear expansion coefficient between the frame material 16 and the base substrate 14 is within the above range, the adhesion between the frame material 16 and the base substrate 14 is excellent.
[0068] [Joining layer 22] The bonding layer 22 is a bonding layer formed by sintering a sintering paste containing metal particles. As the sintering paste, any one of Ag sintering paste containing silver particles, Al sintering paste containing aluminum particles, and Cu sintering paste containing copper particles can be used.
[0069] The above-mentioned sintering paste is provided between the electronic component 12 and the metal thin film 26, and between the base substrate 14 and the metal thin film 26, and then laminated. By a sintering process, the electronic component 12 and the metal thin film 26 are bonded by the bonding layer 22, and the base substrate 14 and the metal thin film 26 are bonded by the bonding layer 22.
[0070] In the bonding layer 22, a sintering network (metallic bond bus) is formed by metal particles, and high thermal conductivity and low electrical resistance are realized. From the viewpoint of improving the bonding property of the bonding layer 22, the metal thin film 26 may be subjected to a surface treatment of plating with a metal contained in the sintering paste. Specifically, in this embodiment, the surface of the metal thin film 26 may be subjected to Ag plating.
[0071] <Power module manufacturing method> The method for manufacturing the power module of this embodiment includes the steps of: preparing a frame material 16; a step of fixing a frame material 16 to an upper surface of a base substrate 14 having an electronic component 12 on one surface thereof so as to surround the electronic component 12; and filling a space surrounded by the upper surface of the base substrate 14 and the frame material 16 with a sealing material 18 to seal the electronic component 12.
[0072] First, the thermosetting resin composition is molded by a known molding method such as compression molding or transfer molding to form a box-shaped frame 16 of a desired size with upper and lower openings.
[0073] Next, an insulating substrate 24 having thin metal films 26 on both sides is mounted on the surface of the base substrate 14 via a sintering paste. Then, an electronic component 12 is mounted on the thin metal film 26 on the other side of the insulating substrate 24 via a sintering paste. Then, a sintering process bonds the electronic component 12 and the thin metal film 26 with the bonding layer 22, and bonds the base substrate 14 and the thin metal film 26 with the bonding layer 22. The conductive pattern on the lower surface of the electronic component 12 is electrically connected to the thin metal film 26 by the bonding layer 22.
[0074] The electrode pattern on the top surface of the electronic component 12 is electrically connected to the metal thin film 26 via wires 28 by wire bonding. Furthermore, a terminal 30 is provided on the surface of the metal thin film 26, making it possible to transmit signals from the electronic component 12 to the outside. Next, a frame member 16 is fixed to the upper surface of the base substrate 14 so as to surround the electronic components 12, the insulating substrate 24, and the like.
[0075] Then, in the region surrounded by the frame material 16, the resin composition is poured so as to cover the electronic components 12, the insulating substrate 24, the metal thin film 26, and the lower parts of the terminals 30, and is cured to form the encapsulant 18. The casting and curing conditions are appropriately selected.
[0076] The base substrate 14 of the resulting structure is connected to an external cooling structure 20 so that heat from the electronic component 12 can be dissipated.
[0077] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted as long as they do not impair the effects of the present invention. EXAMPLES
[0078] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0079] [Examples 1 to 5, Comparative Example 1] In Examples 1 to 5, the raw materials in the amounts shown in Table 1 below were mixed at room temperature using a mixer, and then roll-kneaded at 70 to 100° C. The kneaded mixture was then cooled and pulverized to obtain a granular thermosetting resin composition. The mixture was then tableted under high pressure to obtain a tablet-shaped thermosetting resin composition. In Comparative Example 1, a thermoplastic resin composition containing PPS resin A575W20 (manufactured by Toray Industries, Inc.) was used.
[0080] Resole type phenolic resin: PR-53529 (Sumitomo Bakelite Co., Ltd., weight average molecular weight: 700) Calcium hydroxide (Kawai Lime Industry Co., Ltd.) Magnesium oxide (Kyowa Chemical Industry Co., Ltd.) Glass fiber filler: CS3E479 (manufactured by Nitto Boseki, fibrous filler with an average fiber diameter of 11 μm and an average fiber length of 3 mm) Glass spherical filler: UB-13LA (Unitika, average particle size 45μm) Calcium carbonate: SS#80 (manufactured by Nitto Powder Industries Co., Ltd.) Clay (ECC) Silica: (SIDISTAR (manufactured by ELKEM, average particle size 0.15 μm)) Wax: Stearic acid (NOF Corporation) Pigment: Carbon black #750 (Mitsubishi Chemical)
[0081] [specific gravity] The thermosetting resin compositions of the Examples and Comparative Examples were injected into a mold using a low pressure transfer molding machine ("TEP50-70" manufactured by Fujiwa Seiki Co., Ltd.) under the conditions of a mold temperature of 175°C, an injection pressure of 10.0 MPa, and a curing time of 120 seconds. This resulted in a disk-shaped molded product having a diameter of 50 mmΦ and a thickness of 3 mm. The molded product thus obtained was then post-cured at 175°C for 4 hours to prepare a test piece for evaluating specific gravity. The specific gravity of the obtained disk-shaped molded product was measured using an electronic specific gravity meter ("SD-200L" manufactured by Alpha Mirage Co., Ltd.).
[0082] [Flexural strength / flexural modulus] The thermosetting resin compositions of the examples and comparative examples were injected into a mold using a low pressure transfer molding machine ("TEP50-70" manufactured by Fujiwa Seiki Co., Ltd.) under the conditions of a mold temperature of 175°C, an injection pressure of 10.0 MPa, and a curing time of 120 seconds. As a result, a molded product having a width of 10 mm, a thickness of 4 mm, and a length of 80 mm was obtained. The molded product obtained was then post-cured under the conditions of 180°C and 8 hours. As a result, a test piece for evaluating mechanical strength was prepared. Then, the bending strength (MPa) and bending modulus (GPa) of the test piece at room temperature (25°C) and 150°C were measured in accordance with JIS K 6911.
[0083] [Glass transition temperature, linear expansion coefficient] Using the thermosetting resin compositions of the examples and comparative examples, a molded body of 80×10×4 mm was produced by injection molding under the conditions of gate dimensions: 8×3 mm, injection pressure: 150 MPa, mold temperature: 175° C., and filling time: 4 seconds, with the longitudinal direction being the flow direction, and then the obtained molded product was post-cured under the conditions of 180° C. and 8 hours. A test piece of 10×10×4 mm was cut out from the molded body. Then, a thermomechanical analyzer TMA was used to perform measurements in the range of 80° C. to 120° C. under compression conditions of 5° C. / min. From the measurement results, the glass transition temperature (Tg), the linear expansion coefficient in the flow direction (parallel), and the linear expansion coefficient in the direction perpendicular to the flow direction (vertical direction) were calculated.
[0084] [Case (frame) warpage] The thermosetting resin composition of the example was injection molded under the conditions of gate dimensions: 2×9 mm, injection pressure: 150 MPa, mold temperature: 180° C., and filling time: 4 seconds to produce a box-shaped frame material (height 15 cm×width 50 cm×depth 70 cm) with top and bottom open as shown in Fig. 2(a), and then the obtained frame material was post-cured under the conditions of 180° C. and 8 hours. The thermoplastic resin composition of Comparative Example 1 was injection molded under the conditions of injection pressure: 100 MPa, mold temperature: 135° C. to produce a frame material similar to the above. Next, the obtained frame material was bonded to the upper surface of the copper substrate (linear expansion coefficient α3: 17 ° C. / ppm) with an adhesive, and 35 g of an encapsulating epoxy resin composition (composition of Example 1 described in Japanese Patent Application No. 2023-016277) was injected into the space surrounded by the upper surface of the copper substrate and the inner surface of the frame material, and cured under the conditions of (160 ° C. 1 hour + 180 ° C. 2 hours), and the space was filled with an encapsulating material (linear expansion coefficient α1: 15 ° C. / ppm). Then, as shown in FIG. 2 (b), the surface of the frame material was measured using a 3D image measuring device (VR-5000, manufactured by Keyence Corporation). FIG. 3 shows the measurement images of the frame material surfaces of Example 1 and Comparative Example 1, the surface height display, and the measurement results of the surface shape (warping amount).
[0085] [Table 1]
[0086] As shown in Table 1, it was confirmed that the frame material according to the present invention obtained in the examples had a flexural modulus (150°C) in the range of 6 GPa to 30 GPa, and the occurrence of warping was suppressed. Therefore, it was confirmed that the power module including the frame material according to the present invention has excellent product reliability. [Explanation of symbols]
[0087] 10 Power Module 12 Electronic Components 14 Base board 16 Frame material 18 Encapsulating materials 20 External cooling structure 22 Bonding layer 24 Insulating substrate 26 Metallic Thin Film 28 Wire 30 Terminals
Claims
1. (A) a base substrate having electronic components on one surface thereof; (B) a frame material provided on a surface of the base substrate (A) on which the electronic components are provided so as to surround the electronic components; (C) a sealing material that seals the electronic component in an area surrounded by the frame material (B); A frame material (B) in a power module comprising: A frame material for a power module, wherein the flexural modulus (150°C) of the frame material (B) is 6 GPa or more and 30 GPa or less.
2. 2. The frame material for a power module according to claim 1, wherein the frame material has a bending strength (150°C) of 50 MPa or more and 200 MPa or less.
3. 2. The frame material for a power module according to claim 1, wherein the frame material has a glass transition point of 120° C. or higher.
4. The frame material for a power module according to claim 1 , wherein the frame material (B) contains a phenolic resin.
5. (A) a base substrate having electronic components on one surface thereof; (B) a frame material provided on a surface of the base substrate (A) on which the electronic components are provided so as to surround the electronic components; (C) a sealing material that seals the electronic component in an area surrounded by the frame material (B); A power module comprising: A power module in which the flexural modulus (150 ° C.) of the frame material (B) is 6 GPa or more and 30 GPa or less.
6. The power module according to claim 5 , wherein a value S1 calculated by the following formula is 0.3 or more and 10 or less. Formula: S1 = flexural modulus of frame material (B) (GPa, 150°C) / |(α1-α2)| α1: Linear expansion coefficient of the sealing material (C) in the vertical direction (ppm / ° C.) α2: Linear expansion coefficient of the frame material (B) in the vertical direction (ppm / °C)
7. The power module according to claim 5 , wherein a value S2 calculated by the following formula is 0.4 or more and 10 or less. Formula: S2 = flexural modulus of frame material (B) (GPa, 150°C) / | (α2 - α3) | α2: Linear expansion coefficient (ppm / ° C.) of the frame material (B) in the vertical direction α3: Linear expansion coefficient (ppm / ° C.) of the base substrate (A) in the vertical direction
8. The power module according to claim 5 , wherein the frame material (B) contains a phenolic resin, and the sealing material (C) contains an epoxy resin.
9. A step of preparing a frame material (B); A step of fixing a frame material (B) to an upper surface of a base substrate (A) having electronic components thereon so as to surround the electronic components; and filling a space surrounded by the upper surface of the base substrate (A) and the frame material (B) with a sealant to seal the electronic component. The method for manufacturing a power module, wherein the frame material (B) is made of a phenolic resin composition.
Citation Information
Patent Citations
Insulation case
JP2014116421A